(untitled) (American Journal of Islam and Society, 1996)
Then we put thee on the right way, So follow thou that; And follow not the desires of those who know not. (Qur’an 45: 18) Introduction Western perceptions of Islam have always been colored by their fear of Islamic expansion and the historical rationality of the Crusades. The current preoccupation with the "clash of civilizations" debate and the extraordinary focus on "Islamic fundamentalism" have greatly politicized the discourse on Islam while preventing a fuller understanding of Islam. The tendency among Muslim scholars to allow the West to set the agenda of what should be studied in and about Islam has led to the delay of ijtihad in more important areas, such as Islamic political economy. In the age of modernization, thinkers in the West have rejected Islam as backward looking and as an impediment to economic development. A fair interpretation of Islam, however, includes a complete understanding of the need for development and social welfare. The political economy of Islam, as this paper will present, is a completely humanistic and internally consistent development and welfare-oriented paradigm. In the twentieth century, Islam has survived colonial domination, communist repression, and the rapid spread of liberalism. Today it has a rapidly increasing membership of over one billion and is experiencing a resurgence from Malaysia to Sudan and Algeria and from Iran to the newly independent republics of Central Asia. More and more nations with predominantly Muslim populations are undergoing a burgeoning sense of Islamic consciousness. To some, this is a cohesive global phenomenon with potentially indelible consequences. They see it as a radical movement that is antithetical to Western liberal values and a challenge to their religious zeal to universalize these values. Regardless of the political constructions of Islam’s revival, what is of the essence is that more and more ...